Migration and EU Enlargement: The Case of Ireland V Denmark - GURDGIEV, CONSTANTIN (My University, 2006)
Since the EU enlargement, European migration policies were characterised by a fundamental inconsistency: faced by changes in public opinion toward migrants, the majority of the EU Member States have chosen to restrict the mobility of European citizens despite the increasing economic returns to immigration experienced in the three states (UK, Sweden and Ireland) that opted out of such restrictions. In this paper we compare the experiences with migration in Denmark and Ireland - two states that have exhibited dissimilar attitudes towards migration, and chosen different approaches to migration policy vis-a-vis the Accession States. The importance of this comparison rests on the fact that prior to the Accession, both countries exhibited some of the most liberal immigration policies in the EU. Yet, while Ireland embraced a liberal market-based approach, Denmark chose to favour humanitarian reasons for granting residency. Thus, the two countries represent similar overarching migration flows with differing selection mechanisms prior to the Accession and diametrically opposing policies following the Accession. Using a computable general equilibrium model, we show the differences in economic benefits from international migration for Denmark and Ireland. We attribute the differences in economic gains to the nature of migration flows and labour markets specifics in the two countries. We further discuss various differences between the two states in their approach to migration as potential drivers behind the economic returns to migration experienced in Ireland and Denmark.
PUBLISHED
Keywords: Social Policy; Migration